EKSPLORASI FAKTOR RESILIENSI DI KALANGAN REMAJA BROKEN HOME - Purnamasari, Yuniarti; Saripah, Ipah; Nadhirah, Nadia Aulia (Bimbingan dan Konseling, FKIP, Universitas Nahdlatul Ulama Cirebon, 2025)
It is important for broken home teenagers to have resilience to overcome their various difficulties and problems, as well as develop their welfare. This research aims to reveal the positive side of teenagers from broken home families regarding the factors that influence the formation of resilience in broken home teenagers so that they are able to survive in unpleasant conditions. This research uses a qualitative approach with a case study method regarding the factors that develop resilience. Collection is carried out through interviews, observation and documentation. The participants in this research were two teenagers from a broken home (divorce and no parental role). The research results show that the factors that influence resilience are emotional regulation, controlling impulses, optimism, ability to analyze problems, empathy, self-efficacy, and increasing positive aspects. Based on the research results, it is hoped that guidance and counseling teachers will be able to develop resilience, especially in indicators of optimism, so that they can face life's challenges better.